O mecanismo de priming effect como mediador dos efeitos de interações não-aditivas entre detritos florais e foliares na decomposição - Alencar, Mery Ingrid Guimarães de (2020)
The interaction between litter with different qualities generate non-additive effects on the decomposition, a phenomenon called priming effect (PE). Despite the global relevance of PE for decomposition in ecosystems, generalizations of their effects from the interaction between litter from different plant organs are concentrated in leaf litter and rhizosphere. However, whether and how the priming effect mechanism occurs in the interaction between leaf and floral litter is not yet evident in the literature. Compared to leaves, flowers tend to be organs of less longevity and therefore tend to have a higher concentration of nutrients than leaf litter. Such difference in nutritional quality between the two types of litter must be manifested at both intraspecific and interspecific levels. Thus, this dissertation addresses, in two chapters, the relative importance of effects of floral and leaf litter on the occurrence, magnitude and direction of the priming effect. In the first chapter, we seek to understand the effects of the priming effect at the intraspecific level. For this, we conducted experimental tests with mixtures between floral and leaf litter, for 30 species with wide phylogenetic distribution. The interaction between the litter generated non-additive effects for most treatments, with synergistic and reciprocal interactions (i.e. non-additive effects manifested in both types of debris) in 53% of the species. In the second chapter, we evaluate the relative effect of intra and interspecific variation and their interactions on the magnitude of the priming effect. For this we use an experimental approach with floral and leaf litter of three species decomposing separately and together in all pairs of possible combinations for intra and interspecific. Floral litter showed higher concentrations of important attributes for decomposition, which resulted in higher decomposition rates compared to leaf litter. Functional differences between types of litter generated synergistic effects on decomposition, for most treatments with interaction between flowers and leaves. The major magnitude occurred in interspecific interactions when compared to intraspecific interactions. Despite the widespread occurrence of non-additive effects, we found no relationship between the magnitude of the PE and the functional dissimilarity between leaf and floral debris both intra and interspecifically. The results indicate that the priming effect mechanism is an important mediator of nonadditive effects in the interaction between floral and leaf litter, both at intraspecific and interspecific level. These results are particularly interesting because they alert to the biogeochemical importance of the decomposition of floral litter, both directly (i.e. through the own decomposition), and indirectly (i.e. through the mediation of the decomposition of leaf litter). In this way, plant species that invest heavily in the production of flowers can act as a biogeochemical hotspot in terms of nutrient cycling in terrestrial ecosystems.